Penguatan Profil Pelajar Pancasila Melalui Media Pembelajaran Fisika - Dewi Dewantara; Sarah Miriam; Mustika Wati; Sri Hartini; Abdul Salam M; Surya Haryandi (Jurnal Pemberdayaan Masyarakat, 2024)
Partners, namely members of the Tanah Bumbu Regency Physics “Musyawarah Guru Mata Pelajaran (MGMP)”  forum. This forum is under the auspices of the Education and Culture Office of the South Kalimantan Provincial Government. This forum consists of 23 physics teachers in Tanah Bumbu Regency. The analysis of the situation and problems of partners showed that teachers at the Tanah Bumbu Regency Physics MGMP need to be given reinforcement of the Pancasila Student Profile Through Physics Learning Media at the Tanah Bumbu Regency Physics MGMP. This Community Service uses the Service Learning (SL) method which consists of preparation, implementation, and reflection. The material presented was about the Pancasila Student Profile, the use of learning media in order to strengthen the Pancasila student profile, Introduction and preparation of physics learning media in order to strengthen the Pancasila student profile. The activity was continued with assistance in preparing physics learning media in order to strengthen the Pancasila student profile. The achievement of increasing the empowerment of partners in utilizing media in learning was measured using an observation sheet. Achievement was calculated through the average score obtained. The results of the activity evaluation showed this workshop was considered successful in delivering material and achieving the stated goals